2010
DOI: 10.1016/j.actbio.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological effects of different acrylic intracorneal ring segments in corneal additive surgery

Abstract: a b s t r a c tThe objective of this work was to evaluate the potential use of less stiff materials based on acrylic copolymers of methyl methacrylate/2-ethylhexyl acrylate (MMA/EHA) as devices to correct, stabilize and improve the effect of poly(methyl methacrylate) (PMMA) intracorneal ring segments. MMA/EHA and PMMA intracorneal ring segments were surgically implanted in the corneas of Lohmann Classic hens. The effects of the intracorneal ring segments were assessed by optical measurements and corneal tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In previous studies it was speculated that the ICRS rotates within the cornea, because its base is observed to be oriented with a certain angle respect to the corneal surface. 2,11 Also an accumulation of cells at the ICRS edges has been observed using microscopy, 41 and tissue wound healing was attributed to induce the rotation. However, the disagreement between the orientation of ICRS base and corneal tunnel (triangular ICRSs only) is not a true rotation but rather a result from the plane shape of the rigid ICRS being inserted into the curved soft cornea.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies it was speculated that the ICRS rotates within the cornea, because its base is observed to be oriented with a certain angle respect to the corneal surface. 2,11 Also an accumulation of cells at the ICRS edges has been observed using microscopy, 41 and tissue wound healing was attributed to induce the rotation. However, the disagreement between the orientation of ICRS base and corneal tunnel (triangular ICRSs only) is not a true rotation but rather a result from the plane shape of the rigid ICRS being inserted into the curved soft cornea.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike subtraction techniques, such as excimer laser corneal refractive surgery, ICRS preserve tissue, modifying the cornea without removing tissue or contact with the cornea center. 4 Several classification systems have been proposed for keratoconus staging based on various parameters such as keratometry readings, spectacle refraction, apical corneal thickness, and high-orders aberrations, but until recently there was no grading system to provide an integrated approach for combining multiple morphological parameters along with visual related factors such as visual acuity. 5 Two most widely used grading systems in the literatures are the Amsler-Krumeich (AK) and the Collaborative Longitudinal Evaluation of Keratoconus (CLEK) Study classification systems.…”
Section: Introductionmentioning
confidence: 99%
“…20 The highest hyperopic value at which the retinal reflex was reversed was taken to be the resting refraction. Refractive state measurements were taken preoperatively at 1, 2, and 3 months postimplantation and 1, 2, 3, 4, 5, and 6 months postexplantation.…”
Section: Optical Measurements: Refractive Statementioning
confidence: 99%
“…16 However, there are some differences with regard to the human cornea: first, the cornea is thinner and the diameter is smaller in hen corneas; second, in the hen cornea the collagen lamellae are arranged differently at different depths 17 ; third, hen corneas have a special accommodation mechanism and the wound healing response is quicker than humans. 18 Despite these differences, the hen has been used as an animal model to study wound healing after different surgeries in several studies carried out by us 19,20 and also by other groups. 16,21 These studies have validated the hen as an animal model due to similarities to human wound healing mechanisms following PRK, LASIK and ICRS implantation.…”
Section: Introductionmentioning
confidence: 99%